Islamic and Archaeological Antiquities after the Young Turk Revolution - Shaw, Wendy (Possessors and Possessed, 2003)
By the end of the empire Ottoman museums had come full circle, with military collections regaining supremacy in the production of national identity. Nonetheless, despite all of the political confusion, economic turmoil, and prolonged military struggle of the last decade of Ottoman rule, the archaeological and Islamic museums in İstanbul did not simply manage to stay afloat, they became increasingly important voices for the emergent national struggle. While the Islamic identity of the Ottoman state had been central to Abdülhamid’s political program, it was only during and after the constitutionalist Young Turk Revolution of 1908–10 that concern over Islamic